Fibroblast-secreted hepatocyte growth factor mediates epidermal growth factor receptor tyrosine kinase inhibitor resistance in triple-negative breast cancers through paracrine activation of Met. - Mueller, Kelly L.; Madden, Julie M.; Zoratti, Gina L.; Kuperwasser, Charlotte.; List, Karin.; Boerner, Julie L. (2016)
Introduction: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have shown clinical efficacy in lung, colon, and pancreatic cancers. In lung cancer, resistance to EGFR TKIs correlates with amplification of the hepatocyte growth factor (HGF) receptor tyrosine kinase Met. Breast cancers do not respond to EGFR TKIs, even though EGFR is overexpressed. This intrinsic resistance to EGFR TKIs in breast cancer does not correlate with Met amplification. In several tissue monoculture models of human breast cancer, Met, although expressed, is not phosphorylated, suggesting a requirement for a paracrine-produced ligand. In fact, HGF, the ligand for Met, is not expressed in epithelial cells but is secreted by fibroblasts in the tumor stroma. We have identified a number of breast cancer cell lines that are sensitive to EGFR TKIs. This sensitivity is in conflict with the observed clinical resistance to EGFR TKIs in breast cancers. Here we demonstrate that fibroblast secretion of HGF activates Met and leads to EGFR/Met crosstalk and resistance to EGFR TKIs in triple-negative breast cancer (TNBC).; Keywords: bovine serum albumin, Dulbecco's modified Eagle's medium, epidermal growth factor receptor, enzyme-linked immunosorbent assay, hepatocyte growth factor, phosphate-buffered saline, reduction mammoplasty fibroblasts expressing human hepatocyte growth factor, small hairpin RNA, tyrosine kinase inhibitor, triple-negative breast cancer.; Springer Open.